Raising the level of abstraction deepens your thinking - Hohpe, Gregor (Shortcuts, 2024)
The role of software architects is transforming. Architects now need to combine organizational and technical knowledge to effect change in their company. In these videos, author Gregor Hohpe shares real-world advice and hard-learned lessons from actual IT transformations.